CANNABIS IN SPAIN: A STUDY FROM A GENERALIST PRESS PERSPECTIVE - Santos Diez, María Teresa (2022)
This article analyses the treatment of cannabis as a drug in the Spanish newspapers La Razón, El Mundo, El País and ABC during 2019. Using a content analysis methodology, we identify the sources used, the authorship of the texts, the dominant thematic areas and compare the treatment given by the aforementioned newspapers. The results show a predominance of informative genres with texts signed by the editors or regular collaborators, who use official sources and ignore the point of view of other areas. The main topics are those related to actions classified as crimes (arrests, dismantling, seizures and road safety), and there is a lack of institutional information on addiction prevention campaigns.